From democracy in Africa to African-style democracy - (:unkn) unknown (My University, 2025)
Several decades after independence, democracy is still struggling to take root on the dark continent. For Alexis de Tocqueville (1981; 2019), democracy is the driving force behind political life. It also allows it to breathe, laying the foundations for socio-economic development and freedom for the people. Despite the will of the people and of certain political leaders, democracy gets bogged down mandate after mandate, and political transitions are made painfully, often under the pressure of arms. As a result, literate, Westernized presidents in need of convincing results give way to illiterate brigands who, day in, day out, sell supposed sovereignty to oppressed, starving populations. The comfort of power, corruption and nepotism are just a few of the reasons why democracy has failed to take root in Africa. Keywords: democracy, coup d'état, transition, development, freedom, education
Keywords: African Research